Branding in Pakistani TV Dramas: A Multimodal Analysis (Journal of Asian Development Studies, 2025)
This study investigates the product promotional strategies employed in recent Pakistani television dramas, looking closely at both visual and verbal ways of advertisement. Six famous dramas, including Meem Sy Mohabbat, Dil Wali Gali Main, Ishq Di Chashni, My Dear Cinderella, Chand Tara, and Suno Chanda, were chosen for a more detailed study. Every drama had three to four branded products included in the story by being shown in the scenes and mentioned by the actors. Investigating visuals and verbal elements when products or their brands are featured in dramas, this study explores how visual signs (logos, packaging, and placement) and brand mentions function as effective and natural advertising. This study aims to analyze the role commercial brands play in forming meanings about the product, its usefulness, or its part in society. Multimodal Discourse Analysis (MDA), Kress & van Leeuwen (2001, 2006), is the main framework for this study to analyze product advertisements integrated by using visuals and verbal language in TV dramas. Results show that the brands are placed with purpose, mixed into daily conversations, and even though it helps promote the products. The study shows how media forms, like entertainment, make use of various techniques to change the way consumers perceive brands in ways that connect with their culture.